Adjuvant effect of B domain of staphyloccocal protein A displayed on the surface of hepatitis B virus capsid. Issue 2 (4th September 2015) - Kim, Hyun Jin; Ahn, Keum‐Young; Bae, Kyung Dong; Lee, Jiyun; Sim, Sang Jun; Lee, Jeewon
ABSTRACT: The hepatitis B virus (HBV) capsid‐based recombinant particles, which display both major hydrophilic region of HBV surface antigen (HBV–MHR) and B domain of Staphylococcal protein A (SPAB ), were produced using Escherichia coli as expression host. SPAB was used as an adjuvant to elicit the immune response to HBV–MHR, and its adjuvant effect in the immunized mice was estimated with varying the position and amount of SPAB on the HBV capsid particles. Compared to the emulsified aluminum gel (alum gel) that is a currently commercialized vaccine adjuvant, SPAB caused the significantly higher level of anti‐HBV immunoglobulin G (IgG) titer and seroconversion rate, and notably SPAB at the most surface‐exposed position on the recombinant particle led to the highest immune response. Moreover, SPAB caused much lower ratio of IgG1 to IgG2a compared to alum gel, indicating that helper T‐cell 1‐mediated immune response (responsible for cytotoxic T‐cell stimulation) is relatively more stimulated by SPAB, unlike alum gel that mainly stimulates helper T‐cell 2‐mediated immune response (responsible for B‐cell stimulation). Although HBV–MHR and HBV capsid particle were used as proof‐of‐concept in this study, SPAB can be used as a highly effective adjuvant with other disease‐specific antigens on the surface of other virus‐like particles to produce various recombinant vaccines with high potency. Biotechnol. Bioeng. 2016;113: 268–274. © 2015 Wiley Periodicals, Inc. Abstract : HBV capsid‐based recombinant particles, which display both MHR of HBV surface antigen and SPAB, were prepared to evaluate how functional SPAB is as a vaccine adjuvant to increase the immune response to HBV‐MHR when displayed on HBV capsid. The authors confirmed that the SPAB ‐mediated immune response can be properly modulated by changing the insertion position and amount of SPAB on vaccine particles..